Regulatory Interplay between NFIC and TGF-β1 in Apical Papilla-derived Stem Cells. (May 2014) - He, W.; Zhang, J.; Niu, Z.; Yu, Q.; Wang, Z.; Zhang, R.; Su, L.; Fu, L.; Smith, A.J.; Cooper, P.R.
While transforming growth factor-β1 (TGF-β1) can regulate odontoblast differentiation in tooth crown morphogenesis, its effects on cells including stem cells from the apical papilla (SCAPs) involved in root formation are unclear. Nuclear factor I-C (NFIC) has been implicated in the regulation of root development, and interplay with TGF-β1 signaling has been reported in some cell types. We hypothesize that NFIC and TGF-β1 are important to the behavior of SCAPs and that the interplay between these molecules controls the regulation of the odontogenic differentiation of SCAPs. TGF-β1 inhibited the proliferation of SCAPs and their mineralization. Real-time polymerase chain-reaction (RT-PCR) and Western blot results showed that TGF-β1 significantly decreased osteogenic/dentinogenic gene expression. The inhibition of TGF-β/Smad signaling (SIS3) attenuated the suppressive effect of TGF-β1 on SCAPs. Importantly, overexpression of NFIC antagonized the effects of TGF-β1 on SCAPs, while knockdown of NFIC enhanced these effects, demonstrating a key regulatory role for NFIC in modulating TGF-β1 signaling in SCAPs. We conclude that this interplay between NFIC and TGF-β1 regulates SCAPs behavior and can determine the differentiation of these cells. These signaling interactions help inform the development of regenerative strategies aimed at root growth and development in immature teeth for endodontic treatment.